(untitled) (mathematica didactica, 2010)
The article deals with the so-called Pizza Theorem: A pizza is divided into 2n equiangular pieces by a symmetric pizza knife with n crossing blades. The problem: a fair fifty-fifty partition of the pizza, where each of two persons gets n pieces, but on condition that the center of the knife does not meet the center of the pizza. The problem and a lot of ist variations are being solved and discussed with methods of calculus and geometry. It has a rich didactic potential. Suggestions for lessons in lower and upper secondary level of mathematical education are submitted.